Total Flavonoid Content in Hydro-ethanolic Extract of Sauropus androgynus (L.) Merr Leaves from Three Regions with Different Altitude - Ni Putu Ermi Hikmawanti; Hayati; Yeni Andriyani (Jurnal Jamu Indonesia, 2021)
Sauropus androgynus (L.) Merr (Phyllanthaceae), also known as katuk in Indonesia, is a plant that grows in tropical climates. The study aimed to determine the total flavonoid levels of hydroethanolic extract of katuk leaves from three regions with different altitudes. Dried katuk leaves were macerated using hydroethanolic (the mixture of ethanol:H2O (7:3, v/v)) as solvent extraction at room temperature. Determination of flavonoid levels was carried out by the colorimetry method using AlCl3 reagent. Quercetin was used as a reference. A UV-Visible spectrophotometer measured the absorbance at the maximum wavelength of 434.50 nm. The total flavonoids level of hydroethanolic extract of katuk leaves from a different region with low-altitude (Bogor), medium-altitude (Sleman), and high-altitude (Bandung) are 8.56±0.63 mgQE/g, 4.67±0.30 mgQE/g, and 9.72±0.24 mgQE/g, respectively. Thus, it can be concluded that there are differences in total flavonoid levels of hydroethanolic extract of katuk leaves from three regions with different altitudes.